Triglyceride-Rich Lipoprotein Cholesterol and Risk of Cardiovascular Events Among Patients Receiving Statin Therapy in the TNT Trial. Issue 8 (21st August 2018) - Vallejo-Vaz, Antonio J.; Fayyad, Rana; Boekholdt, S. Matthijs; Hovingh, G. Kees; Kastelein, John J.; Melamed, Shari; Barter, Philip; Waters, David D.; Ray, Kausik K.
Abstract : Background: Mendelian randomization data suggest that the genetic determinants of lifetime higher triglyceride-rich lipoprotein-cholesterol (TRL-C) are causally related to cardiovascular disease and therefore a potential therapeutic target. The relevance of TRL-C among patients receiving statins is unknown. We assessed the relationship between TRL-C and cardiovascular risk, and whether this risk was modifiable among patients receiving statins in the TNT trial (Treating to New Targets). Methods: Patients with coronary heart disease and low-density lipoprotein cholesterol (LDL-C) 130 to 250 mg/dL entered an 8-week run-in phase with atorvastatin 10 mg/d (ATV10). After this period, participants with LDL-C <130 mg/dL entered the randomized phase with ATV10 (n=5006) versus atorvastatin 80 mg/d (ATV80, n=4995). The primary end point was coronary heart disease death, nonfatal myocardial infarction, resuscitated cardiac arrest, or stroke (major adverse cardiovascular events [MACE]). TRL-C was calculated as total cholesterol minus high-density lipoprotein cholesterol minus LDL-C. The effect of atorvastatin on TRL-C was assessed during the run-in phase (ATV10) and randomized phase (ATV80 versus ATV10). The risk of MACE was assessed across quintiles (Q) of baseline TRL-C (and, for comparison, by baseline triglycerides and non–high-density lipoprotein cholesterol) during the randomized period. Last, the association between TRL-C changes with atorvastatin and cardiovascular risk was assessed by multivariate Cox regression. Results: ATV10 reduced TRL-C 10.7% from an initial TRL-C of 33.9±16.6 mg/dL. ATV80 led to an additional 15.4% reduction. Cardiovascular risk factors positively correlated with TRL-C. Among patients receiving ATV10, higher TRL-C was associated with higher 5-year MACE rates (Q1=9.7%, Q5=13.8%; hazard ratio Q5-versus-Q1, 1.48; 95% confidence interval, 1.15–1.92; P -trend<0.0001). ATV80 (versus ATV10) did not significantly alter the risk of MACE in Q1-Q2, but significantly reduced risk in Q3-Q5 (relative risk reduction, 29%–41%; all P <0.0250), with evidence of effect modification ( P -homogeneity=0.0053); results were consistent for triglycerides ( P -homogeneity=0.0101) and directionally similar for non–high-density lipoprotein cholesterol ( P -homogeneity=0.1387). Last, in adjusted analyses, a 1 SD percentage reduction in TRL-C with atorvastatin resulted in a significant lower risk of MACE (hazard ratio, 0.93; 95% confidence interval, 0.86–1.00; P =0.0482) independent of the reduction in LDL-C and of similar magnitude to that per 1 SD lowering in LDL-C (hazard ratio, 0.89; 95% confidence interval, 0.83–0.95; P =0.0008). Conclusions: The present post hoc analysis from TNT shows that increased TRL-C levels are associated with an increased cardiovascular risk and provides evidence for the cardiovascular benefit of lipid lowering with statins among patients who have coronary heart disease with high TRL-C. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT00327691. Abstract : Supplemental Digital Content is available in the text.